Regional Regulatory Mechanism of the Protection of Pet Animals (the example of Council of Europe) - Zubchenko, Nadiia; Зубченко, Надежда Игоревна (Юридичний вісник, 2013)
The article dedicated to the regional regulatory mechanism of the protection of pet animals on the example of Council of Europe. The main Conventional instruments for the protection of pet animals highlighted. The participation of Ukraine in the activity of Council of Europe in the field of protection of pet animals researched.

Стаття присвячена розгляду регіонального механізму регламентації захисту домашніх тварин на прикладі Ради Європи. Описані основні конвенційні документи щодо захисту домашніх тварин. Досліджено участь України у діяльності Ради Європи по захисту тварин.

Статья посвящена рассмотрению регионального механизма регламентации защиты домашних животных на примере Совета Европы. Описаны основные конвенционные документы относительно защиты домашних животных. Рассмотрено участие Украины в деятельности Совета Европы по защите животных.
Zubchenko N. Regional Regulatory Mechanism of the Protection of Pet Animals (the example of Council of Europe) / N. Zubchenko // Юридичний вісник. - 2013. - № 2. - С. 145-150.
Keywords: regulatory mechanism; protection of animals; conventions of Council of Europe; regional level of regulation; cruelty; регуляторный механизм; конвенции Совета Европы; защита животных; жестокое обращение; жорстоке поводження; захист тварин; регуляторний механізм